Familial chronic lymphocytic leukemia in Israel: A disproportionate distribution among Ashkenazi Jews. (3rd May 2017) - Zada, Mor; Lerner, Daniele; Piltz, Yuval; Perry, Chava; Avivi, Irit; Herishanu, Yair
Abstract: Background: Relatives of patients with chronic lymphocytic leukemia (CLL) are at increased risk of developing CLL. Familial CLL is defined as more than one case of CLL among blood relatives, a phenomenon reported in approximately 5%‐10% of all CLL patients. Objective: Given the known predisposition of CLL among Ashkenazi Jews, we studied the features of familial CLL in an Israeli population. Methods: This is a retrospective study, in which we reviewed the demographics, clinical characteristics, and outcomes of a total of 332 patients with CLL/small lymphocytic lymphoma. Results: Familial CLL was recorded in 41 cases (12.3%) of the patients. The age at diagnosis was younger in patients with familial CLL (by almost 3.5 years). Familial CLL was strongly associated with Ashkenazi Jewish origin. Patients with familial CLL more commonly presented with higher hemoglobin and lower serum β‐2‐microglobulin levels. No significant differences were detected between sporadic and familial CLL in disease stage, time to treatment, second cancers, or overall survival. Conclusion: Familial cases of CLL in an Israeli population show a disproportionate ethnic distribution toward Jews of Ashkenazi origin. The clinical characteristics and the overall outcome are not substantially different from sporadic cases.